Enduring Neuroprotective Effect of Subacute Neural Stem Cell Transplantation After Penetrating TBI - Kassi, Anelia A. Y.; Mahavadi, Anil K.; Clavijo, Angelica; Caliz, Daniela; Lee, Stephanie W.; Ahmed, Aminul I.; Yokobori, Shoji; Hu, Zhen; Spurlock, Markus S.; Wasserman, Joseph M; Rivera, Karla N.; Nodal, Samuel; et al. (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) is the largest cause of death and disability of persons under 45 years old, worldwide. Independent of the distribution, outcomes including disability and associated huge societal costs. The heterogeneity of TBI and complicated biological response have helped discover the limitations of current approach to TBI management. Five decades of efforts have made significant progress in reducing TBI associated mortality but very little progress in mitigation of disability. Failure to scale up results to single center clinical trials with neuroprotective agents, surgical and medical approaches led to consensus that international collaborative comparative effectiveness research is the way forward. Current focus of the field is on generating rich, comprehensive human dataset with demographic, clinical, genomic, proteomic, imaging, and detailed outcome data across multiple time points. In addition to address, the shortcomings of preclinical research the Operation Brain Trauma Therapy (OBTT), a multicenter, pre-clinical drug-screening consortium test effectiveness of promising therapies with a spectrum of established TBI models at experienced centers measuring both conventional outcomes and serum biomarker levels in a standardized manner. Knowledge from such efforts suggest that cellular response to TBI disability stems from: (i) variety of cell death processes initiated by injury, (ii) incomplete debris clearance that provokes aberrant immune response leading to spatiotemporal magnification of the injury. Decades of research have brought the field to the limits of systemic and pharmacological means of disrupting the TBI process; recent advances in technology necessitate revisiting interventions at cellular level. In this review, based on the efforts of our lab and current literature, we present evidence to support our interpretation of TBI pathophysiology. We also provide (i) a survey of TBI epidemiology and summary of current care, (ii) findings of past neuroprotective clinical trials present possible reasons for failure using evidence from human and preclinical TBI pathophysiology studies, (iii) unmet need and unproven treatments, (iv) rationale for cell therapy-based neuroprotection approach to reduce the TBI burden.